The effect of nanosilver in carriers based on polymer/inorganic hybrids on the quality and safety of edible chicken eggs - L. V. Shevchenko; Y. Y. Dovbnia; T. B. Zheltonozhskaya; N. M. Permyakova; L. M. Vygovska; V. O. Ushkalov (Regulatory Mechanisms in Biosystems, 2021)
One of the modern antibacterial agents that are an alternative to antibiotics are nanoparticles of noble metals, including silver. To reduce their toxicity, cumulative effect and prolong the effect in animals, there is ongoing work on development and improvement of the methods for their synthesis using various carriers, including those based on polymer/inorganic hybrids. In this study, the quality and safety of edible eggs were determined on Hy-Line laying hens using W36 solutions of nanosilver in carriers based on polymer/inorganic hybrids (AgNPs/SPH) in the concentration of 0.0, 1.0 and 2.0 mg/L of water (0.0, 0.2 and 0.4 mg per hen per day) three times with 10 day interval. We determined that one-, two- and three-time feeding of nanosilver in doses of 0.0, 0.2 and 0.4 mg per hen per day did not affect water consumption, feed, egg productivity, as well as dry matter content, crude protein, fat, ash, and calcium and phosphorus in eggs for 30 days. Contamination of the surface of the shell and yolks of eggs with mesophilic aerobic and facultative anaerobic microorganisms (MAFAnM) did not depend on the dose and duration of consumption of the nanosilver drug by laying hens. The nanosilver drug in doses of 0.0, 0.2 and 0.4 mg per hen per day did not affect the contamination of the egg shell surface with microorganisms of genera Citrobacter, Klebsiella, as well as Escherichia coli, Proteus mirabilis, Salmonella spp., Staphylococcus aureus and S. epidermidis. When administered orally, nanosilver in the dose of 0.2 mg per hen per day did not change the number of symbiotic microorganisms of genera Bifidobacterium and Lactobacillus, while and the dose of 0.4 mg per hen daily slightly reduced the number of microorganisms of genus Lactobacillus in the hens’ manure. The obtained data can be used for further research to determine the effective dose and interval of application of nanosilver preparations to poultry for preventive and therapeutic measures, taking into account the preservation of the microbiome of the digestive system of hens.